Threat of Nomophobia to Prospective Teachers : An Empirical Study - Saxena, Manoj K.; Chauhan, Sumit (JOURNAL OF INDIAN EDUCATION, 2023)
In the present times, smartphones have become an essential part of everyone’s life and prospective teachers are not an exception to it. The study was trying to find out the threat of nomophobia to prospective teachers in Kangra district of Himachal Pradesh. The present study was carried out to know how many prospective teachers suffer from nomophobia. Lottery method was used to select 300 prospective teachers from various B.Ed. colleges in Kangra district of Himachal Pradesh. The data were collected by using a self-developed questionnaire. In this study, the researcher tried to assess the comfort or discomfort level of prospective teachers in absence of their smartphone. The results show that the majority of prospective teachers feel discomfort or disappointment when the internet speed is reduced. Most of the prospective teachers felt disheartened when they were unable to get the information through their smartphones.